Cloud Computing and Information Infrastructure: Emerging Possibilities- A SWOT Analysis - Paul, Prantosh K.; Kumar, Kalyan; Chatterjee, Dipak (Journal of Information and Knowledge, 2014)
Cloud Computing (CC) can trace its root to Grid Computing which is responsible for rapid provisioning of resources. Actually both Cloud and Grid services provide scalability as functionality. Practically in Cloud users, storage, networks and data transferred at a particular time, and can be de-allocated depending upon need. CC is one of the important emerging methods for Virtualization. In this utilization computing practice; software, hardware, application, information technology infrastructure and other resources are desired through virtualized and networked services. The paper describes about CC; its basic issue, characteristics, need, importance: to know basics about information infrastructure and integrating role of CC for improved functioning of Information Sector.